A question of scent: lavender aroma promotes interpersonal trust - Sellaro, Roberta; van Dijk, Wilco W.; Paccani, Claudia Rossi; Hommel, Bernhard; Colzato, Lorenza S. (Frontiers in Psychology, 2015)
A previous study has shown that the degree of trust into others might be biased by inducing either a more “inclusive” or “exclusive” cognitive-control mode. Here, we investigated whether the degree of interpersonal trust can be biased by environmental factors, such as odors, that are likely to impact cognitive-control states. Arousing olfactory fragrances (e.g., peppermint) are supposed to induce a more exclusive, and calming olfactory fragrances (e.g., lavender) a more inclusive state. Participants performed the Trust Game, which provides an index of interpersonal trust by assessing the money units one participant (the trustor) transfers to another participant (the trustee), while being exposed to either peppermint or lavender aroma. All participants played the role of trustor. As expected, participants transferred significantly more money to the alleged trustee in the lavender as compared to the peppermint and no aroma conditions. This observation might have various serious implications for a broad range of situations in which interpersonal trust is an essential element, such as cooperation (e.g., mixed-motives situations), bargaining and negotiation, consumer behavior, and group performance.